The Collection of the Sumerian Temple Hymns - Sjöberg, Åke W. (1969)
with a Study by Gene B. Gragg: The Keš Temple Hymn, p. 155-188; in collaboration with Miguel Civil, Erica Reiner, Edmond Sollberger; $20.00.